Postoperative thrombotic effects of tranexamic acid in open heart surgery - SARAÇOĞLU, AYTEN (SPRINGER LONDON LTD, 2019)
Background Following the administration of tranexamic acid, the occurrence of thromboembolic events is a controversial issue. Aims In this retrospective cohort study, we aimed to determine the possible thromboembolic complications due to tranexamic acid as a prophylactic method in patients undergoing open heart surgery. Methods The data of 172 adult patients undergoing open heart surgery were analyzed. All patients received tranexamic acid at a dose of 50 mg/kg. The patients were divided into 3 groups as multiple-valve surgery (group 1), coronary bypass alone (group 2), and coronary bypass with valve surgery (group 3). The amount of blood transfusion, bleeding in intra- and postoperative period, and the presence of thromboembolic events including myocardial infarction, stroke, pulmonary embolism, and deep vein thrombosis were investigated. Results Patient demographics and duration of surgery were not significantly different in groups (p > 0.05). Hb, Htc, INR, and platelet levels of all groups did not differ significantly (p > 0.05). In total, 7 patients underwent reexploration. Postoperative DVT, stroke, and seizure were not seen at all. There was no statistically significant difference between groups in terms of the amount of blood transfusion, drainage, or peritoneal hematoma. The length of hospital stay and the mortality rate did not differ (p > 0.05). Conclusions In patients receiving tranexamic acid infusion at 50 mg/kg dose, reexploration rates remained at 4.1% even after major cardiac surgeries. No thrombosis, stroke, or seizure were reported. Our findings support that tranexamic acid is a safe drug which has positive effect on reducing perioperative bleeding.
Keywords: Cardiac surgery; Thrombosis; Tranexamic acid; BLOOD-TRANSFUSION; MANAGEMENT